Calculating the momentum enhancement factor for asteroid deflection studies. (2017) - Heberling, Tamra; Gisler, Galen; Plesko, Catherine; Weaver, Robert
Abstract: The possibility of kinetic-impact deflection of threatening near-Earth asteroids will be tested for the first time in the proposed AIDA (Asteroid Impact Deflection Assessment) mission, involving NASAs DART (Double Asteroid Redirection Test). The impact of the DART spacecraft onto the secondary of the binary asteroid 65803 Didymos at a speed of 5 to 7 km/s is expected to alter the mutual orbit by an observable amount. The velocity transferred to the secondary depends largely on the momentum enhancement factor, typically referred to as beta. We use two hydrocodes developed at Los Alamos, RAGE and PAGOSA, to calculate an approximate value for beta in laboratory-scale benchmark experiments. Convergence studies comparing the two codes show the importance of mesh size in estimating this crucial parameter.